RANCANG BANGUN SISTEM INFORMASI PENGADUAN KERUSAKAN PERANGKAT ODC BERBASIS WEB DENGAN METODE WATERFALL PADA PT TELKOM AKSES JAKARTA SELATAN - Adi Saputra; Yono Cahyono (CV. Multi Kreasi Media, 2022)
PT Telkom Access is one of Telkom's subsidiaries which is engaged in the construction and management of network infrastructure services which was established in 2012. Telkom Cipete STO (Automatic Telephone Center) is one of the PT Telkom Access STOs spread throughout Indonesia which is a switching-device telecommunications as a connector and breaker of information that is sent in a centralized and distributed manner and has its address at Cilandak – South Jakarta. In running its business, STO Telkom Cipete must be able to ensure that the Optical Distribution Cabinet (ODC) spread over the work coverage area of ​​STO Telkom Cipete can work properly. For this reason, it is necessary to carry out periodic maintenance and inspections in case of disturbances to ensure that all services provided by Telkom can work properly. The reporting process by the existing Operations Team Leader is all done via telegram messages to the existing telegram working group which will be read and processed by the maintenance administrator and forwarded back to field technicians so that repairs can be made to the problematic Optical Distribution Cabinet (ODC). received report messages. This reporting system often causes problems with report messages that are often missed and unread because of the large number of messages in the telegram group. In addition, the damage reporting history is not recorded properly so that the search for past damage history data is difficult to find. The process design method is focused on model development using UML (Unified Model Language) and using the PHP programming language, as well as Xampp v3.2.2 with Apache as the web server and MySQL as database storage. This research produces an application that is able to record all damage reporting data so that damage reporting is not missed and provides good notifications to speed up the damage repair process and is able to make it easier for admins to search for damage reporting history data that has occurred as a reference for future improvements.